The Blackwell Encyclopedia of Writing Systems - Coulmas, Florian (Hoboken : John Wiley & Sons, 1999)
Annotation This is an encyclopedia of writing systems, scripts and orthographies of all the world's major languages, past and present. It provides both a fully illustrated description of over 400 writing systems and an account of the study of writing in many different disciplines, from anthropology to psychology.
Trade
Keywords: Writing - Encyclopedias